Possibilities of development of the wine tourism in the guarantee of origin Jerez-Xerry-Sherry and Manzanilla of Sanlucar of Barrameda and vinegar of Sherry - Resumen Autores (Boletín de la Asociación de Geógrafos Españoles)
Resumen